Analisis Pemanfaatan Sistem Informasi Manajemen Rumah Sakit (SIMRS) Pada RRSUD DOK II Jayapura - Ruth Molly; Meyrolen Itaar (APTIKOM SUMSEL, 2021)
The development and progress of information technology are now very broad. For an agency/company, the information used as the basis for administration and data processing is an application system in various fields that are required to use the information system. Hospital information systems have an important role in clinical and administrative services. Hospitals that use an electronic-based system (SIMRS) are designed to integrate the hospital's main functions into one unified system that is stored in a central database.